2014
DOI: 10.12691/ajams-2-6-2
|View full text |Cite
|
Sign up to set email alerts
|

The Exponentiated Lomax Distribution: Different Estimation Methods

Abstract: This paper concerns with the estimation of parameters for the Exponentiated Lomax Distribution ELD.Different estimation methods such as maximum likelihood, quasi-likelihood, Bayesian and quasi-Bayesian are used to evaluate parameters. Numerical study is discussed to illustrate the optimal procedure using MATHCAD program (2001). A comparison between the four estimation methods will be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…businessandeconomics.mq.edu.au. We compare the goodness-of-fit results of the L-Claim distribution with the two-parameter Lomax distribution and three-parameter power Lomax (P-Lomax) distribution [2], transmuted Lomax (T-Lomax) distribution [3], and exponentiated Lomax (E-Lomax) distribution [4]. We estimate the unknown parameters of the fitted distributions via the maximum likelihood method using the Rscript adequacy model with the "Nelder-Mead" method; see Appendix.…”
Section: Application Of the L-claim To Vehiclementioning
confidence: 99%
See 1 more Smart Citation
“…businessandeconomics.mq.edu.au. We compare the goodness-of-fit results of the L-Claim distribution with the two-parameter Lomax distribution and three-parameter power Lomax (P-Lomax) distribution [2], transmuted Lomax (T-Lomax) distribution [3], and exponentiated Lomax (E-Lomax) distribution [4]. We estimate the unknown parameters of the fitted distributions via the maximum likelihood method using the Rscript adequacy model with the "Nelder-Mead" method; see Appendix.…”
Section: Application Of the L-claim To Vehiclementioning
confidence: 99%
“…is distribution has been proved as a significant alternative to the exponential, Weibull, and gamma distributions to model heavy-tailed data sets. Due to the importance and applicability of the Lomax distribution, it has been extensively generalized and modified to obtain a more flexible extension of the Lomax distributions, for example, power Lomax distribution [2], transmuted Lomax distribution [3], exponentiated Lomax distribution [4], weighted Lomax distribution [5], exponential Lomax distribution [6], gamma Lomax distribution [7], Poisson Lomax distribution [8], an extended Lomax distribution [9], Marshall-Olkin extended Lomax [10], exponentiated Weibull Lomax [11], Kumaraswamy generalized power Lomax [12], Marshall-Olkin length biased Lomax [13], Gompertz Lomax [14], half-logistic Lomax [15], Gumbel Lomax [16], transmuted Weibull Lomax [17], and transmuted exponentiated Lomax [18].…”
Section: Introductionmentioning
confidence: 99%
“…Such as Folks (1983), Lehmann and Shaffer (1988), Calabria and Pulcini (1990), Khan, et al (2008) and Khan (2010). A number of studies have showed some details about the exponentiated Lomax distribution for example Abdul-Moniem (2012), Ashour and Eltehiwy (2013), Salem (2014), El-Bassiouny et al (2015) introduced exponentiated Lomax distribution and Ashour and Eltehiwy (2013).…”
Section:  - ...mentioning
confidence: 99%
“…where Θ = (a, θ T ) T is the parameter space of the expg family, a > 0 is the new induced shape parameter, and θ is the parameter space of distribution of G. This family have been used for several distributions of G among them we refer to Lomax [1], modified Weibull [33], generalized class of distributions [54], generalized Birnbaum-Saunders [57], generalized inverse Weibull ( [66], [81], [82], [104]), Weibull ( [122], [123], [124], and [127]), general exponentiated type [128], Gumbel [129], gamma [131], Lomax [169], and Pareto [178].…”
Section: Introductionmentioning
confidence: 99%